Sport Massage for Lower Back Pain (Study of Treatment Model Development for Sports Health) - Surya Adi Saputra; Ari Wibowo Kurniawan; Supriyadi Supriyadi (INSPIREE: Indonesian Sport Innovation Review, 2023)
The purpose of the study. The purpose of this research is to create a model of the Sports Massage program by application, specifically for sufferers of Lower Back Pain. the novelty of this product is: the sports massage program model is usually only given to athletes for recovery, but this time the sports massage is made specifically for the treatment of lower back pain sufferers. Materials and methods. This research method uses the Research and Development method. with a Flow Chart consisting of 7 stages, to produce a product that has been tested and is suitable for use, starting from: (1) Finding ideas (2) Making planning manuscript designs (3) Making initial product models (3) Revision of product I (4) Prototype production (5) Small group trials (6) Revision II (7) Large group trials (8) Revision III (9) Product refinement and producing final products. Results. The results showed that there was effectiveness in using the digital sports message model as evidenced by the data showing that there were 9 samples in the good category and 1 sample in the very good category. While in the treatment of massage not based on the application, there were 3 samples with the sufficient category. And the development of this digital sports massage model has the advantage of video content and books can also be downloaded so that people with lower back pain can do it for free in various places even at home. Conclusions. From the research that has been done, it can be seen that sufferers of lower back pain need a solution for handling massage that makes it easier for sufferers to do so, so the development of this digital sports massage model has good effectiveness in use.